Improving disaster response efforts with decision support systems. (15th November 2006) - Thompson, Steven; Altay, Nezih; Green III, Walter G.; Lapetina, Joanne
As evidenced by Hurricane Katrina in August, 2005, disaster response efforts are hindered by a lack of coordination, poor information flows, and the inability of disaster response managers to validate and process relevant information and make decisions in a timely fashion. A number of factors contribute to current lacklustre response efforts. Some are inherent to the complex, rapidly changing decision-making environments that characterise most disaster response settings. Others reflect systematic flaws in how decisions are made within the organisational hierarchies of the many agencies involved in a disaster response. Slow, ineffective strategies for gathering, processing, and analysing data can also play a role. Information technology, specifically decision support systems, can be used to reduce the time needed to make crucial decisions regarding task assignment and resource allocation. Decision support systems can also be used to guide longer-term decisions involving resource acquisition as well as for training and the evaluation of command and control capability.